2012
DOI: 10.2528/pier12032403
|View full text |Cite
|
Sign up to set email alerts
|

Four Dimensional Reconstruction Using Magnetic Induction Tomography: Experimental Study

Abstract: Abstract-Magnetic Induction Tomography (MIT) is a relatively new and emerging type of tomography techniques that is able to map the distribution of all three passive electrical properties (PEPs). Its non-invasive and contactless features make it an attractive technique for many applications compared to the traditional contact electrode based electrical impedance tomography. Recently, MIT has become a promising monitoring technique in industrial process tomography, and the area of the research interest has move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Similar approaches have been reported in microwave and ultrasonic imaging [24,25]. Several other inverse and imaging problems can potentially benefit from limited region tomography method proposed in this paper, including but not limited to [27][28][29][30][31][32][33][34][35]. In [25], a pre-processing method was used to apply a bandpass filtering to multiple-frequency data for microwave tomography.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Similar approaches have been reported in microwave and ultrasonic imaging [24,25]. Several other inverse and imaging problems can potentially benefit from limited region tomography method proposed in this paper, including but not limited to [27][28][29][30][31][32][33][34][35]. In [25], a pre-processing method was used to apply a bandpass filtering to multiple-frequency data for microwave tomography.…”
Section: Image Reconstructionmentioning
confidence: 99%
“…Nowadays, electromagnetic modeling has become a useful tool for analyzing target scattering characteristic, and especially it has played an important role in landmine detection for the Ground Penetrating Radar (GPR) system [19]. Based on the simulated results of the improved Physical Optics (PO) method and the BoomSAR experimental results [20], the Army Research Laboratory (ARL) investigates the 1-dimension features of metal landmine.…”
Section: Electromagnetic Scattering Characteristics Of Landminementioning
confidence: 99%
“…In this case, the temporal algorithm can be implemented into the inverse solver to include the correlation information between the measurement frames. It is demonstrated that the temporal algorithm can effectively improve the noise performance and the stability of the images [26,27]. Each temporal image is reconstructed based on the correlation between several images that are obtained using Equation (7).…”
Section: Inverse Problemmentioning
confidence: 99%